ANALISIS VARIABILITAS BASE FLOW INDEX SUB-DAS CILIWUNG PADA POS DUGA AIR BENDUNG KATULAMPA (PERIODE 1998 â 2013) - Badia Anugerah, Gilbert
Base flow is one of the important components of the parameters in the hydrological function of a watershed, which comes from ground water discharge and plays an important role during the dry season or drought. Separation of base flow in the sub-Ciliwung is done by using smoothed minima. Smoothed minima method developed by the Institute of Hydrology (1980) to analyze the base flow through the value of Base Flow Index (BFI) which is derived from the daily river discharge data. Daily discharge data that been used are the data from the period 1998 - 2013. BFI value of Ciliwung upstream part ranged from 49.9 to 89.6%. Spearman-Conley shows that the trend of the BFI value has increased, Factors that affecting the estimated base flow variability associated with human activity directly to the river such as changes in land cover and land use, groundwater exploration and there are also natural factors like climate anomalies are supporting a large variation of base flow each year. The increase in the contribution base flow in the sub-Ciliwung able to overcome the problems of drought in the dry season, but the capacity of hydrological be things that must be considered in the future to maintain the stability of maintaining groundwater recharge capabilities. The implementation of green infrastructure method is fairly effective method to establish a system of sustainable environmental management. Implementation of green infrastructure ranging from upstream activities when rain falls to the management of surface water runoff to flow into the soil or water bodies. This method is necessary in order to maintain the quality, quantity, and continuity of Ciliwung to fulfill the needs of raw water for surrounding communities.